Stroke: Exploring the pathophysiology and sleep disorders (Research, Society and Development, 2023)
Cerebrovascular accident (CVA) is characterized by a focal neurological deficit resulting from brain damage of an ischemic or hemorrhagic nature. The objective of this work is to address the pathophysiology of the disease, describing clinical manifestations in patients with a previous history of stroke, in addition to establishing a correlation with sleep disorders. The present study is an integrative review of the literature, of a descriptive nature, which established that the main risk factors for the development of the disease are: hypertension, smoking, alcoholism and atrial fibrillation. The most common involvement is the ischemic type, representing 80% of cases, occurring mainly in adult and elderly patients, with a higher incidence after the age of 65, doubling every decade after the age of 55. The diagnosis is clinical, with findings of numbness of the face and limbs, mental confusion, imbalance and gait changes. Treatment involves thrombolysis and thrombectomy, both guided by neuroimaging. Added to this, there is an intimate relationship between the disease and sleep disorders, including parasomnias, insomnia and hypersomnia. Furthermore, post-stroke sleep disorders affect rehabilitation and quality of life, increasing the recurrence rate of this pathology.